Innovative Limonoid-Based Targeted Therapy: Citrus-Derived Compounds for Selective Apoptosis and Cell-Cycle Control in Estrogen-Dependent Breast Cancer - Barack Ndenga (Publisher, 2025)
Estrogen receptor–positive (ER⁺) breast cancer remains a critical oncological challenge due to therapeutic resistance, adverse effects of endocrine treatments, and cellular heterogeneity. This study introduces an innovative targeted therapy model utilizing limonoids extracted from Citrus limon, focusing on their selective apoptotic and cell-cycle regulatory properties. Employing AutoEvoChem™ V2.0, a molecular evolutionary simulation platform developed by the author, we conducted ligand–receptor docking, evolutionary binding optimization, and probabilistic conformational scanning of principal limonoids—including limonine, nomiline, and obacunone—against key molecular targets: ERα, ERβ, CDK4/6, Bcl-2, and caspase regulatory domains. Computational simulations reveal that these limonoids exhibit preferential affinity for the ERα ligand-binding domain, triggering allosteric destabilization that attenuates estrogen-driven transcriptional activity. Additionally, limonoids enhance recruitment of caspase-3 and caspase-9 and upregulate p53 expression, while simultaneously downregulating cyclin D1 and CDK4/6 complexes, thereby inducing G1-phase cell-cycle arrest. These predictions delineate a dual anticancer mechanism consisting of (1) selective apoptosis activation in ER⁺ cells and (2) suppression of cell-cycle progression through checkpoint modulation. Overall, these findings position Citrus limon–derived limonoids as promising low-toxicity candidates for novel targeted therapies against hormone-dependent breast cancer, with particular potential in low-resource clinical settings.
This work presents an innovative molecular hypothesis on the targeted anticancer potential of citrus-derived limonoids in estrogen-dependent breast cancer. Using AutoEvoChem™ V2.0, a proprietary evolutionary molecular modeling platform developed by the author, this study explores the selective induction of apoptosis and cell-cycle arrest by limonin, nomilin, and obacunone. Computational simulations predict strong interactions with the ERα ligand-binding domain, significant modulation of CDK4/6 activity, and activation of mitochondrial apoptotic cascades. The findings highlight a dual-action mechanism—hormonal pathway modulation combined with proliferation control—supporting limonoids as promising low-cost candidates for next-generation targeted therapy. This publication contributes to the emerging field of natural-molecule-based precision oncology and positions citrus phytoconstituents as potential molecular scaffolds for anticancer drug discovery.